2015
DOI: 10.1097/fjc.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotection of Baicalein Against Oxidative Stress-induced Cardiomyocytes Injury Through the Nrf2/Keap1 Pathway

Abstract: Baicalein is one of the major flavonoids found in the root of Scutellaria baicalensis Georgi. Previous studies suggest that baicalein displays protective effect on experimental cardiac models in vitro and in vivo. However, the mode of action remains unclear. Here, we showed that baicalein conferred cardioprotective effect against oxidative stress-induced cell injury in H9c2 cells and human embryonic stem cells-derived cardiomyocytes. Immunoprecipitation with anti-NF-E2-related factor 2 (Nrf2) antibody in baica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…We have recently demonstrated that the protective effects of baicalein, an active component of S. baicalensis , against oxidative stress-induced damage through activation of Nrf2 signaling pathway (Choi et al, 2016[10]). Other researchers have obtained similar results (Zhang et al, 2012[46]; Cui et al, 2015[14]). However, the protective effects and molecular mechanisms involved in oxidative stress-induced skin damages are still unclear.…”
Section: Introductionsupporting
confidence: 64%
“…We have recently demonstrated that the protective effects of baicalein, an active component of S. baicalensis , against oxidative stress-induced damage through activation of Nrf2 signaling pathway (Choi et al, 2016[10]). Other researchers have obtained similar results (Zhang et al, 2012[46]; Cui et al, 2015[14]). However, the protective effects and molecular mechanisms involved in oxidative stress-induced skin damages are still unclear.…”
Section: Introductionsupporting
confidence: 64%
“…Recently, it has been proven that baicalein protected H9c2 cardiomyocytes and also human embryonic stem cells-derived cardiomyocites (hESC-CMs) against oxidative stress-induced cell injury. Baicalein (10, 30 µM) decreased ROS generation and the number of death cells and activated Nrf2 pathway [62]. …”
Section: In Vitro Effects Of Polyphenols Against Oxidative Stress-mentioning
confidence: 99%
“…In addition to these traditional dosage forms, there are also dietary supplements available containing either extracts of Scutellaria baicalensis or baicalein as pure compound. Due to extraordinatel structural element of three proximate hydroxygroups in ring A, baicalein has potent radicalscavenging effects 2 and has previously been shown to mediate antioxidative effects in mammalian cells by activation of the Nrf2 signaling pathway [3][4][5][6][7][8] . Using Caenorhabditis elegans it has been shown that baicalein reduces ROS accumulation and prolongs the life span of this model organism: baicalein extends the mean, median and maximum lifespans by 45, 57 and 24%, respectively 3 .…”
Section: Introductionmentioning
confidence: 99%